Analysis Of The Influence Of Artificial Intelligence On Business Innovation (Literature Review Study) - Setiawan, Jodi; Hendayana, Yayan (Dinasti Publisher, 2024)
Technology plays a very important role in a business, one of which is Artificial Intelligence (AI). This research was conducted to determine the impact of AI on business innovation and the challenges faced in its implementation. This research is carried out using the Literature Review method. Data in this research is collected through various electronic media. The findings in this study are AI can automate routine tasks, increase accuracy and efficiency, and provide in-depth data analysis. Although AI replaces many human analytical skills, the need for intuitive and empathetic abilities is increasing. This shows the importance of a new approach in human-machine interaction, where AI and human skills work synergistically to provide optimal service. But in its implementation, AI has obstacles such as costs, privacy, quality of human resources, and legal regulations. Overall it can be underlined that Artificial Intelligence (AI) affects the business of business.